PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI DAN KOMPETENSI GURU TERHADAP KEPUASAN KERJA GURU TAMAN KANAK - KANAK SE-KECAMATAN MANTRIJERON YOGYAKARTA TAHUN PELAJARAN 2012/2013 (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The Influence of Transformational Leadership, the Organizational Culture and the Competence on the Job Satisfaction of Teacher of Mantrijeron Kindergaten (TK)2012/2013 Years. Thesis, the Post Graduate Program of Sarjana Wiyata Taman Siswa University of Yogyakarta.The purposes of this study were the impact of (1) The influence of variables transformational leadership, organizational culture and competence of teachers on the job satisfaction of teachers, (2) the influence of transformational leadership on job satisfaction of teachers, (3) the influence of organizational culture on the job satisfaction of teachers, and (4) the influence of teacher competence on the job satisfaction of teachers.The variable in this study were transformational leadership, organizational culture and teacher competence and job satisfaction. The population in this study was kindergarten teachers at all-district of Mantrijeron Yogyakarta totaling 75 people. Sampling in this study using total sample. The data collection technique using questionnaires. The analysis tool used was multiple linear regression and Partial Corulation.